مظاهر التحول الرقمي للعملية التعليمية في كليات تنمية المجتمع بالجامعات السودانية: دراسة ميدانية بكلية تنمية المجتمع جامعة القرآن الكريم وتأصيل العلوم - ود مدني 2023 م. - المبارك، حسن الفاتح الحسين محمد الحسين (مركز البحث وتطوير الموارد البشرية - رماح, 2024)
تهدف الدراسة إلى التعرف على مظاهر التحول الرقمي للعملية التعليمية في كليات تنمية المجتمع بالجامعات السودانية، وهي دراسة ميدانية بكلية تنمية المجتمع جامعة القرآن الكريم وتأصيل العلوم- ود مدني- 2023م، استخدم فيها الباحث المنهج الوصفي التحليلي، وأداة الاستبانة التي تم تصميمها وتوزيعها إلكترونيا، على عينة عشوائية تكونت من (100) عضوا من أعضاء هيئة التدريس بكلية تنمية المجتمع في جامعة القرآن الكريم وتأصيل العلوم؛ وهي تشكل نسبة (35) من مجتمع الدراسة الكلي؛ الذي بلغ (289) عضوا، ولتحليل بيانات الدراسة استخدم برنامج الحزم الإحصائية للعلوم الاجتماعية (Spss)، وتلخصت مشكلة الدراسة في السؤال الرئيس: ما مظاهر التحول الرقمي للعملية التعليمية في كليات تنمية المجتمع بالجامعات السودانية؟، كما طرحت الدراسة التساؤلات التالية: ما اتجاهات أعضاء هيئة التدريس بكليات تنمية المجتمع في الجامعات السودانية نحو التحول الرقمي؟، وما المعوقات التي تواجه كليات تنمية المجتمع بالجامعات السودانية في تطبيق التحول الرقمي؟، توصلت الدراسة إلى النتائج التالية: تحقق مظاهر التحول الرقمي للعملية التعليمية في كليات تنمية المجتمع بالجامعات السودانية بمتوسط عام (3.694) وبدرجة تقديرية كبيرة، وتحقق اتجاهات أعضاء هيئة التدريس بكليات تنمية المجتمع في الجامعات السودانية نحو التحول الرقمي بمتوسط عام (3.591) وبدرجة تقديرية كبيرة. وتحقق المعوقات التي تواجه كليات تنمية المجتمع بالجامعات السودانية في تطبيق التحول الرقمي بمتوسط عام (3.797) وبدرجة تقديرية كبيرة. في ضوء النتائج السابقة أوصت الدراسة بتدريب أعضاء هيئة التدريس على التعامل مع مطلوبات التحول الرقمي بكليات تنمية المجتمع، والعمل على ترسيخ ثقافة الرقمنة بين أعضاء هيئة التدريس العاملين بالجامعات السودانية، وتوفير بيئة ومعينات التحول الرقمي بكليات تنمية المجتمع. The study aims to identify the aspects of digital transformation of the educational process in community development colleges at Sudanese universities. It is a field study at the Faculty of Community Development, University of the Holy Quran and Taseel of Science- Wad Madani- 2023. The researcher used the descriptive analytical approach, and the questionnaire tool that was designed and distributed electronically; on a random sample consisting of (100) members of the Faculty of Community Development at University of the Holy Quran and Taseel of Science; which constitutes a percentage (35%) of the total study community; which reached (289) members. To analyze the study data, the Statistical Package for Social Sciences (Spss) program was used. The study problem was summarized in the main question: What are the aspects of digital transformation of the educational process in Faculties of community development at Sudanese universities? The study also raised the following questions: What are the attitudes of faculty members in Faculties of community development at Sudanese universities towards digital transformation? And what are the obstacles facing Faculties of community development at Sudanese universities in implementing digital transformation? The study reached the following results: The aspects of digital transformation of the educational process in Faculties of community development at Sudanese universities are achieved with an overall average of (3.694) and a large appreciative degree, and the attitudes of faculty members in Faculties of community development at Sudanese universities towards digital transformation are achieved with an overall average (3.591) and a large appreciative degree. And the obstacles facing Faculties of community development.at Sudanese universities in implementing digital transformation are achieved with an overall average (3.797) and a large appreciative degree. In light of the previous results, the study recommended training faculty members to deal with the requirements of digital transformation in Faculties of community development., working to establish a digitization culture among faculty members working at Sudanese universities, and providing an environment and means for digital transformation in Faculties of community development.
Keywords: تكنولوجيا المعلومات -- التحول الرقمي -- العملية التعليمية -- السودان